2010
DOI: 10.1096/fj.09-146746
|View full text |Cite
|
Sign up to set email alerts
|

Opioid modulation of cell proliferation in the ventricular zone of adult zebra finches (Taenopygia guttata)

Abstract: Besides modulating pain, stress, physiological functions, motivation, and reward, the opioid system has been implicated in developmental and adult mammalian neurogenesis and gliogenesis. In adult male songbirds including zebra finches, neurons generated from the ventricular zone (VZ) of the lateral ventricles are incorporated throughout the telencephalon, including the song control nuclei, HVC, and area X. Although the endogenous opioid met-enkephalin is present in neurons adjacent to the VZ and is upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 122 publications
2
15
0
Order By: Relevance
“…Thus, the evaluation of the developing (and mature) song in comparison with the tutor song memory may be left-side lateralized, and perhaps mediated via neurotrophins such as BDNF [55], local synthesis of estradiol in NCM in response to hearing song [56], [57], or by neuromodulators involved in reward and reinforcement, such as dopamine and opioid peptides [58], [59], [60], [61]. These transmitter types have been associated with regulating neurogenesis and new neuron survival [60], [62], [63], [64] and have been shown to function in a hemisphere-specific manner [65], [66], [67] although their role in NCM has not been determined [68]. Regardless of the specific trophic mechanism regulating new neuron survival, it must be turned on in an asymmetric way, either because producing a good imitation engages the hemispheres differentially (perhaps through a matching mechanism), or because the trophic process induced by a good imitation is itself asymmetrical.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the evaluation of the developing (and mature) song in comparison with the tutor song memory may be left-side lateralized, and perhaps mediated via neurotrophins such as BDNF [55], local synthesis of estradiol in NCM in response to hearing song [56], [57], or by neuromodulators involved in reward and reinforcement, such as dopamine and opioid peptides [58], [59], [60], [61]. These transmitter types have been associated with regulating neurogenesis and new neuron survival [60], [62], [63], [64] and have been shown to function in a hemisphere-specific manner [65], [66], [67] although their role in NCM has not been determined [68]. Regardless of the specific trophic mechanism regulating new neuron survival, it must be turned on in an asymmetric way, either because producing a good imitation engages the hemispheres differentially (perhaps through a matching mechanism), or because the trophic process induced by a good imitation is itself asymmetrical.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, OPRM1 may influence embryonic development of the amygdala and, subsequently, its function. It has been shown that Oprm1 is expressed very early on in the embryonic rat brain, including the amygdaloid complex, 52 and that opioids may inhibit neurogenesis 53 (Figure 3, right pathway).…”
Section: Discussionmentioning
confidence: 99%
“…Not only the administration of compounds that interact with the opioid system modulate neurogenesis (see introduction ), it has been shown that μ and k opioid receptors play a modulatory role in the differentiation of stem-cell-derived neuronal progenitors [ 45 ] and that μ opioid receptor proteins are expressed in neuroepithelia of the lateral ventricles and radial glia in the embryonic mouse brain [ 46 ]. Mu and delta opioid receptors are expressed in the ventricular zone of adult zebra finches [ 47 ] as well, and opioid receptors and mRNA of different opioids are expressed in the proliferative zones in the fetal rat brain [ 48 ]. Based on the evidence described above, it is possible that opioids released during paced mating could directly influence proliferative zones and induce neurogenesis.…”
Section: Discussionmentioning
confidence: 99%